De l’exubérance végétale à la prédation animale (Altre Modernità, 2012)
It is paradoxically reductive to summarize the bachelardian imaginary of the four fundamental elements. Not only the elements themselves are declined in a variety of materials, but also the bachelardian dynamic is open to the size of a cosmos that can not be reduced to the logic of a quadrangulation. In this context, for the philosopher, the vegetal world also seems to be an inexhaustible source of references and rêveries, which constitute a main pole of meditation. Naturally, references to the plant world appear dispersed in the work of the philosopher: the “aerial tree”, the root, the vine, the water lilies. They are not less multiplied and subtly recurring. Thus Bachelard talks about “notre végétalisme profond” (our deep vegetality). It is necessary to consider the meaning of this enigmatic formula. And this is even more important since the philosopher has always kept himself to the edge of the animal world, to which, after all, he rarely refers to, and in front of which he repeatedly expresses a kind of surprising reluctance. It may be possible that it is not adapted to what, for Bachelard, is more essential while he proceed with is work to a “philosophie du repos” (philosophy of rest). We can also make a disturbing hypothesis: is animality, full of the “Will to Live” that Schopenhauer placed at the heart of his system? Is it ontologically close to that troubled humanity the philosopher feels a very ambiguous sympathy for? Bachelardian vegetality would it be the opposite of what we might call problematic humanism?